Strategic Human Resource Management In Clean Water Management At District Jeneponto, South Sulawesi - Herlina Sakawati; Muh Nur Yamin; Sulmiah Sulmiah; Widyawati Widyawati (Indonesian Association for Public Administration (IAPA), 2019)
Problems of water supply in coastal areas become difficult job for government, especially local government. Required a variety appropriate strategies to cope with water scarcity. one of them with the implementation of HRM with a view to improving the performance of employees that will impact on organizational performance. This study was conducted to see the HRM strategy to applied water management in Jeneponto. Descriptive qualitative research method was chosen to manage the data collected from observation, interviews and secondary data collection. The results from this research is that HRM strategies in the management of clean water as seen from indicators such as: 1) Recruitment and Selection System; 2) Training and Development; 3) Performance and Appraisal System; and 4) Compensation System; 5) Retention Plans and Culture has not been able to improve performance in the management of clean water in Jeneponto district, South Sulawesi. Lack of attention to education and training influences employee creativity in finding clean water supply solutions. In addition, the delay in provision of employee benefits reduces motivation and performance of employees in providing solutions to problems that occur in the management of PDAMs in Jeneponto district.